(untitled) (City: History, Culture, Society, 2018)
As the people of the Middle Ages thought in symbolic categories, this symbolism was imposed on the notion of human life. In Europe, it had a distinct Christian colouration and was associated with the symbolism of numbers. This was reflected as well in the idea of the stages of human life, the number of which ranged from three to seven. Childhood, which was the first in this scheme, lasted from birth to adolescence, that is until reaching puberty. For the medieval people who thought concretely, just tangible things were important. It is not surprising, therefore, that the notion of attaining adulthood was not so much based on the formal number of years as on the real external physiological features. However, over time, such a ‘visual’ determination of the age of the person recedes into the background. Childhood has been linked to a guardianship that has received much attention in the city law codes of the early modern period. Anyone who could not manage their lives and property could count on it. In the Middle Ages, childhood had no place, and until the 12th century, children were hardly depicted. The appearance of the post-mortem images of children in the 16th century was evidence of a change in the emotional attitude to them. This change was reflected in the city law codes of the late 16th century. They protected the right of a child to life and property, even of the unborn or born but not survived child. The born and baptized child was already a complete person with soul and likeness of God. The German town law protected children from too severe punishment, first of all from execution. It was believed that before reaching a certain age the children were unconscious creatures, so they could not deliberately commit crimes. And punishment to death was unacceptable for unconscious wrongdoing. The city law codes in the Polish-Lithuanian Commonwealth of 16th and early 17th centuries reflected the evolution of ideas about childhood from the late Middle Ages to the early modern era. Although they refer to the legal norms of previous epochs, they contain many provisions which appeared under the influence of Humanism and the Reformation. As a result of deeper Christianization of morality at the turn of the Middle Ages and modern era, a new attitude to childhood appears, as to a special and important stage in human life. Therefore, as of the 16th century, there were special articles about children in legal codes. The city law begins to protect the interests of children by considering various aspects, in particular, the rights of the unborn but conceived child, of the children of ‘righteous bed’, orphans, etc., the children’s property interests, their lives and future.